Survey of Lawyers in the Metropolitan New York Media Market, 1989 - Seron, Carroll ([Verlag nicht ermittelbar], 1993)
The purpose of this data collection was twofold. The survey was designed to ascertain the attitudes of attorneys regarding new techniques for obtaining clients, such as media advertising and solicitation, as well as their attitudes toward pro bono service, and to test whether attitudinal differences are related to demographic or organizational characteristics of the profession. A second purpose of the study was to serve as a screener to identify a group of attorneys in solo and small-firm practice who use new types of business-getting techniques. Variables in the collection include respondent attitudes toward advertising, unions, and pro bono cases, information on type of firm, number of attorneys in the firm, type of legal practice and legal specialty, and demographic information such as religious affiliation, membership in local clubs or associations, college attended, marital status, number of children, income, number of years practicing law, and parents' occupations.